A Look at the Future and an Open Call for Scientific Community - Tarlacı, Sultan (Journal of NeuroPhilosophy, 2023)
What we call science is the systematization of information obtained from nature. Nature has had its own laws from the beginning. Some of these laws are easy to express, while others stretch our understanding and even our sense of logic. Our efforts to understand nature and its workings, that is our production of scientific knowledge, will never end. We may never truly understand the workings of nature, or get close to the real truth. Therefore, it is ridiculous to behave as if we knew all of the workings of nature and to say “this is not scientific; it is in conflict with the (known) laws of science”. The clearest example of this is when we see the workings of quantum physics in biological structures. When nature is working, it does not know the laws of our science and doesn’t even take notice of them. Nature even sometimes winks at us with “anomalies”. We learn from nature but we cannot impose on nature the laws we have learned from it.